When separation is not the answer: Breastfeeding mothers and infants affected by COVID‐19 - Cecília Tomori; Karleen Gribble; Aunchalee E.L. Palmquist; Mija‐Tesse Ververs; Marielle S. Gross (Wiley, 2020)
Abstract The World Health Organization (WHO) has provided detailed guidance on the care of infants of women who are persons under investigation (PUI) or confirmed to have COVID‐19. The guidance supports immediate post‐partum mother-infant contact and breastfeeding with appropriate respiratory precautions. Although many countries have followed WHO guidance, others have implemented infection prevention and control (IPC) policies that impose varying levels of post‐partum separation and discourage or prohibit breastfeeding or provision of expressed breast milk. These policies aim to protect infants from the potential harm of infection from their mothers, yet they may fail to fully account for the impact of separation. Global COVID‐19 data are suggestive of potentially lower susceptibility and a typically milder course of disease among children, although the potential for severe disease in infancy remains. Separation causes cumulative harms, including disrupting breastfeeding and limiting its protection against infectious disease, which has disproportionate impacts on vulnerable infants. Separation also presumes the replaceability of breastfeeding-a risk that is magnified in emergencies. Moreover, separation does not ensure lower viral exposure during hospitalizations and post‐discharge, and contributes to the burden on overwhelmed health systems. Finally, separation magnifies maternal health consequences of insufficient breastfeeding and compounds trauma in communities who have experienced long‐standing inequities and violence, including family separation. Taken together, separating PUI/confirmed SARS‐CoV‐2‐positive mothers and their infants may lead to excess preventable illnesses and deaths among infants and women around the world. Health services must consider the short‐andlong‐term impacts of separating mothers and infants in their policies.